SisNasLitbang Academic Social Network Features Recomendation with User Centric Approach - Vita Pusvita (BBPSDMP KOMINFO MAKASSAR, 2018)
The discrepancies between research activities and the national strategic policy of development and science and technology impact on less useful results of research and abandoned government policies/programs. One of the causes is the absences of media which that can build interactions between researchers/academics, governmennt and business entities. Therefore, it needs a social network that can help interaction and collaboration between the three types of users. The purpose of this study is to determine the technical features required in the proposed social network site. This research is done by observation method and literature study based on user centric approach. This research produces social networking features based on user types, ie researchers / academics, government, and business entities. Recomendation features for researchers / academics focus on the needs of researchers. While the government and business entities have features related to supporting research activities and utilize the results of research.